If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = y Solving 2 = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 2 + -1y = y + -1y Combine like terms: y + -1y = 0 2 + -1y = 0 Add '-2' to each side of the equation. 2 + -2 + -1y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1y = 0 + -2 -1y = 0 + -2 Combine like terms: 0 + -2 = -2 -1y = -2 Divide each side by '-1'. y = 2 Simplifying y = 2
| 5x+3+7x=4x-9 | | 8(x+5)-2(x+17)=0 | | 6x-2-9x=-23 | | 4(8)+7y=60 | | 5w+4(w-8)=4 | | 7(-3)+3y=30 | | -y/2+3=0 | | 4z^4-6z^3-18z^2=0 | | 16k^2-25=0 | | -4x+2=-22 | | 3(x+8)=5+4x-9 | | -42x+8=50 | | 6v+2=9v+14 | | 8=5-a | | 9y-30=5y-6 | | 8+3x^2-10x=0 | | 13+4y=9 | | 57(5)-8y=261 | | 2x+13=-1 | | 9m+2=20 | | 18u-5+29=6u-27 | | -3y+2=-10y+30 | | 3(x+5)+2(3x-1)=4 | | 112-9x=164-37x | | 3x^2-10x+3=-5 | | 117-9x=8x+19 | | x^4-7x^3+6x^2+68x-120=0 | | 4x+4=-5x+7 | | 117-9x=8x-19 | | -2(4+x)+11=2(x+4)+1 | | 3+t=17 | | 3.5x-2(x+4)=5.4 |